DESKRIPSI KINERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN (SUATU STUDI DI KECAMATAN MALALAYANG MANADO) - Katuuk, Jerry Jackson (HOLISTIK, Journal Of Social and Culture, 2013)
Residence in a State has a very important role as human resources capable of turning the wheels of development of a nation. In managing the population administration, and its relation to the needs of the community about their rights as a resident or citizen, then the government should be running one of the essential functions, which provide public services, particularly the population administration services to meet people's rights as citizens.Â There are internal factors District government organization Â that can inhibit or support the achievement of the performance of Civil Affairs Ministry, namely: factor structure, factor culture and human resource factors.Keywords : population, administration, development